2014
DOI: 10.1093/carcin/bgu235
|View full text |Cite
|
Sign up to set email alerts
|

CYP2A6 reduced activity gene variants confer reduction in lung cancer risk in African American smokers—findings from two independent populations

Abstract: We investigated genetic variation in CYP2A6 in relation to lung cancer risk among African American smokers, a high-risk population. Previously, we found that CYP2A6, a nicotine/nitrosamine metabolism gene, was associated with lung cancer risk in European Americans, but smoking habits, lung cancer risk and CYP2A6 gene variants differ significantly between European and African ancestry populations. Herein, African American ever-smokers, drawn from two independent lung cancer case-control studies, were genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 37 publications
5
56
0
Order By: Relevance
“…Tan et al suggested that CYP2A6 gene deletion increased lung cancer risk in a Chinese population [16]. In contrast, it has been reported that the CYP2A6 deficient allele was a factor associated with reduced lung cancer susceptibility in Japanese, Bangladeshi, and African American cohorts [10e12, 28,29]. On the other hand, no association between CYP2A6 genotypes and lung cancer risk was found in several other studies [15,17,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Tan et al suggested that CYP2A6 gene deletion increased lung cancer risk in a Chinese population [16]. In contrast, it has been reported that the CYP2A6 deficient allele was a factor associated with reduced lung cancer susceptibility in Japanese, Bangladeshi, and African American cohorts [10e12, 28,29]. On the other hand, no association between CYP2A6 genotypes and lung cancer risk was found in several other studies [15,17,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of CYP2A6 alleles to genotype depends largely on the allele frequencies within the population under study [4,16,17,26]. For statistical analyses individuals are often separated by genotype into predicted reduced or normal CYP2A6 metabolic activity groups [5,6] with the caveat that activity predictions may be substrate specific. Gene variants affecting the amount of CYP2A6 protein (e.g.…”
Section: Cyp2a6 Genotyping Project Considerationsmentioning
confidence: 99%
“…risk factor for lung cancer among Caucasian, African American and Japanese smokers [5][6][7][8], and CYP2A6 enzymatic activity, which is influenced by genetic polymorphisms, has been investigated as a tool for optimizing the selection of smoking cessation pharmacotherapy [9][10][11].…”
mentioning
confidence: 99%
“…Recently, several additional CYP2A6 alleles that are more common among African-Americans have been detected and characterized (Mwenifumbo, Zhou, Benowitz, Sellers, & Tyndale, 2010). In studies on lung cancer susceptibility involving two independent African-American populations, CYP2A6-decreased activity alleles were associated with a significantly decreased risk of lung cancer though, slightly unexpectedly, subgroup analysis suggested the decreased risk related only to males in both community groups with no effect for females (Wassenaar et al, 2015). The numbers of female cases were lower than males but this seems unlikely to explain the relatively large difference seen between the genders.…”
Section: Cyp2a6mentioning
confidence: 99%